Botanical composition of beef cow diets shifts when native range infested with sericea lespedeza (Lespedeza cuneata) is supplemented with corn steep liquor - Garrett W. Preedy; K. C. Olson; Leigh W. Murray; Walter H. Fick (Kansas Agricultural Experiment Station Research Reports, 2014)
Corn steep liquor supplementation indicated that a higher percentage of sericea lespedeza plants were defoliated in pastures grazed by corn steep liquor-supplemented cows than in pastures grazed by unsupplemented cows; however, it was unknown if defoliation was related directly to grazing activity of cows. Therefore, our objective was to evaluate the effects of supplemental corn steep liquor on botanical composition of the diets of beef cows grazing native tallgrass rangeland infested with sericea lespedeza in the Kansas Flint Hills.
Keywords: Cattlemen& #x27; s Day; 2014; Kansas Agricultural Experiment Station contribution; no. 14-262-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1101; Beef Cattle Research; 2014 is known as Cattlemen& #x27; s Day; Beef; Corn steep liquor; Lespedeza cuneata; Grazing; Diet